INKLYUZIV TÁLIMNIŃ INNOVACIALÍQ PARADIGMASÍ: SOCIALLASTÍRÍW, INTEGRACIYALÍQ QATNASÍQLAR HÁM IMKANIYATLARDÍ INSTITUCIONLASTÍRÍW - Bekimbetova, G.R. (SCIENCE and SOCIETY, 2025)
The article provides information on technologies for improving the effectiveness of inclusive and home-based education. In particular, interactive platforms and teaching methods were mentioned for engaging students with disabilities in education.